142 Surgeon-administered ilio-inguinal and pudendal nerve blocks for vulval oncology surgery: an evaluation with visual analogue pain scoring. (13th November 2020) - Maguire, P; Shahabuddin, Y; Gleeson, N
Abstract : Introduction: Surgery for vulval cancer includes sampling diagnostic, excisional biopsy and extensive radical surgery. The vulva and perineum are innervated by branches from the ilio-inguinal and pudendal nerves. We describe our experience of axon nerve blocks and outcomes including postoperative pain scores following surgeon administered intraoperative ilio-inguinal and pudendal nerve blocks. Methods: Ilio-inguinal and pudendal nerve block has become routine practice for women undergoing vulval surgery in our cancer centre. In a retrospective chart review, clinical and demographic data, postoperative visual analogue pain scores and use of analgesia were recorded. Results: Eighteen women were included in the analysis. Their median age was 67 (range 34–81) years and thirteen (72%) were over 60 years. Visual analogue scores ranged from 0 to 3 for 17 patients from day 0–1 and 15 patients from days 2–5. Two patients had pain scores > 4 on one or more postoperative day: one had chronic arthralgia and one had received a lower volume of bupivicaine compared to our routine practice. Figure 1 summarizes postoperative analgesia usage for the 18 women. Conclusion: Ilio-inguinal and pudendal nerve block is a feasible and effective strategy for postoperative pain management in women undergoing vulval surgery.